Post-marketing safety surveillance of vortioxetine hydrobromide: a pharmacovigilance study leveraging FAERS database - Zhang, Ying; Sun, Shengzhu; Ning, Yunhong (Frontiers in Psychiatry, 2025)
BackgroundVortioxetine hydrobromide is a widely prescribed medication for the treatment of major depressive disorder (MDD), primarily exerting its antidepressant effects by inhibiting the reuptake of serotonin (5-HT).The objective of this study was to investigate adverse events (AEs) associated with vortioxetine hydrobromide through data mining in the FDA Adverse Event Reporting System (FAERS) to enhance clinical safety.MethodsWe collected FAERS data from Q3 2013 to Q1 2024 for data cleansing. Disproportionality analysis was employed to quantify relevant AEs associated with vortioxetine. Reported Ratio of Ratios (ROR) was utilized for identifying risk signals within the FAERS data. We employed the System Organ Classes (SOCs) and selected the Preferred Terms (PTs) from the Medical Dictionary for Regulatory Activities (MedDRA version 26.1).ResultsA total of 11,298 cases were reported as "primary suspected (PS)" for vortioxetine hydrobromide. Notably, at the systemic organ level (SOC) level, the adverse effects associated with vortioxetine hydrobromide involved 27 systemic organoid classes (SOCs).We identified 150 significantly disproportionate Preferred Terms (PTs) that met all four algorithms.ConclusionThis study identified adverse events (AEs) associated with vortioxetine. Our findings offer valuable insights for optimizing the use of vortioxetine hydrobromide and reducing potential side effects, serving as a reference for its rational and safe clinical application.